2010
DOI: 10.3168/jds.2010-3167
|View full text |Cite
|
Sign up to set email alerts
|

Field comparison of real-time polymerase chain reaction and bacterial culture for identification of bovine mastitis bacteria

Abstract: Fast and reliable identification of the microorganisms causing mastitis is important for management of the disease and for targeting antimicrobial treatment. Methods based on PCR are being used increasingly in mastitis diagnostics. Comprehensive field comparisons of PCR and traditional milk bacteriology have not been available. The results of a PCR kit capable of detecting 11 important etiological agents of mastitis directly from milk in 4h were compared with those of conventional bacterial culture (48h). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(145 citation statements)
references
References 20 publications
6
123
0
3
Order By: Relevance
“…Relatively higher numbers of E. coli isolates were obtained in conventional method (37.87%) than molecular technique (35.94%). Similar finding was also reported by Koskinen et al (2010) who reported culture identified a species not targeted by the PCR test in 44 samples from clinical mastitis and in 9 samples from subclinical mastitis and dissimilar with Salauddin (2015) who reported all isolates of E. coli were 16S rRNA positive. Multi-drug resistant E. coli isolates were found for 10 commonly used and market available antibiotics.…”
Section: Antibiogram Studysupporting
confidence: 76%
“…Relatively higher numbers of E. coli isolates were obtained in conventional method (37.87%) than molecular technique (35.94%). Similar finding was also reported by Koskinen et al (2010) who reported culture identified a species not targeted by the PCR test in 44 samples from clinical mastitis and in 9 samples from subclinical mastitis and dissimilar with Salauddin (2015) who reported all isolates of E. coli were 16S rRNA positive. Multi-drug resistant E. coli isolates were found for 10 commonly used and market available antibiotics.…”
Section: Antibiogram Studysupporting
confidence: 76%
“…However, this technology failed to identify some of the primary mastitis pathogens in 17.9% of the samples which may also be related to the prolonged transport time. Negative results of up to 12% were also reported for other PCRbased assays compared with culture (Koskinen et al, 2010). Otherwise, primary pathogens, such as Strep.…”
Section: Discussionmentioning
confidence: 87%
“…Similar ranges were obtained when PCR-based molecular methods were compared with culture (Paradis et al, 2012;Spittel and Hoedemaker, 2012). However, molecular methods have been shown to higher detection potential than culture (Koskinen et al, 2009;Koskinen et al, 2010). We also show that the rapid detection of barely cultivatable and slow-growing mastitis pathogens, such as M. bovis, by PCR/ESI-MS represents a major advantage for veterinarians in preventing the spread of the disease within respective herds (Aebi et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Although the culture of milk is considered as a gold standard test for mastitis diagnosis, there are several disadvantages associated with bacterial culture, including no bacterial yielding from truly subclinically infected cows due to presence of high number of leukocytes or presence of preservatives or residual therapeutic antibiotics in submitted samples. A further recognized disadvantage of culture is that about 25 to 45% of all milk samples yield no bacterial growth even after two days of incubation (Koskinen et al, 2010). Moreover, microbiological culture of milk is time consuming and species identification by standard biochemical methods requires more than 48 h to be completed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, microbiological culture of milk is time consuming and species identification by standard biochemical methods requires more than 48 h to be completed. Due to the above-mentioned limitations of cultural methods, Polymerase Chain Reaction (PCR) has been developed to identify various mastitis pathogens (Koskinen et al, 2010). The progress of PCR based techniques supplies a talented option for the rapid detection of different microorganisms.…”
Section: Introductionmentioning
confidence: 99%